Антиоксидантные свойства фуллеренолов. Биолюминесцентный мониторинг - Сачкова А. С. Анна Сергеевна; Ковель Е. С. Екатерина Сергеевна; Чурилов Г. Н. Григорий Николаевич; Кудряшева Н. С. Надежда Степановна (2015, 2015)
Заглавие с экрана